Independent tuning of size and coverage of supported Pt nanoparticles using atomic layer deposition. Issue 1 (December 2017) - Dendooven, Jolien; Ramachandran, Ranjith; Solano, Eduardo; Kurttepeli, Mert; Geerts, Lisa; Heremans, Gino; Rongé, Jan; Minjauw, Matthias; Dobbelaere, Thomas; Devloo-Casier, Kilian; Martens, Johan; Vantomme, André; et al.
Abstract Synthetic methods that allow for the controlled design of well-defined Pt nanoparticles are highly desirable for fundamental catalysis research. In this work, we propose a strategy that allows precise and independent control of the Pt particle size and coverage. Our approach exploits the versatility of the atomic layer deposition (ALD) technique by combining two ALD processes for Pt using different reactants. The particle areal density is controlled by tailoring the number of ALD cycles using trimethyl(methylcyclopentadienyl)platinum and oxygen, while subsequent growth using the same Pt precursor in combination with nitrogen plasma allows for tuning of the particle size at the atomic level. The excellent control over the particle morphology is clearly demonstrated by means of in situ and ex situ X-ray fluorescence and grazing incidence small angle X-ray scattering experiments, providing information about the Pt loading, average particle dimensions, and mean center-to-center particle distance. The performance of supported nanoparticle catalysts is closely related to their size, shape and interparticle distance. Here, the authors introduce an atomic layer deposition-based strategy to independently tune the size and coverage of platinum nanoparticles with atomic-level precision.